Genomic epidemiology and phenotypic characterisation of Salmonella enterica serovar Panama in Victoria, Australia. - Samriddhi Thakur; Sarah L Baines; Cheryll M Sia; Mary Valcanis; Louise M Judd; Benjamin P Howden; Hayley J Newton; Danielle J Ingle (PLoS Neglected Tropical Diseases)
Salmonella enterica serovar Panama, a causative agent of non-typhoidal salmonellosis (NTS), is one of several serovars that causes invasive NTS disease (iNTS) in humans. S. Panama is an understudied pathogen, with its pathobiology poorly understood. It is a predominant iNTS serovar in Australia, a high-income country with high rates of salmonellosis, where S. Panama has been documented to have a high odds ratio (13.9-15.26) for causing iNTS. This study investigates the genomic epidemiology and antimicrobial resistance profiles of all S. Panama isolates recovered in Victoria, Australia, between 2000 and 2021. We examined the infection dynamics of S. Panama in seven isolates, representing the genetic diversity of the study population. Two sub-lineages, encompassed within a previously described Asian lineage, were identified. Multi-drug resistance (resistance to ≥3 drug classes) was detected in 46 (51.7%) Australian isolates. The plasmid-mediated colistin resistance gene, mcr1.1, was detected in one Australian S. Panama isolate, carried by an IncI plasmid previously reported in Salmonella and Escherichia coli isolates collected from poultry in South-East Asia. Examination of the intracellular replication dynamics of S. Panama isolates demonstrated diverse phenotypes. In THP-1 derived macrophages, despite low host cell uptake, S. Panama showed higher replication rates over time compared to S. enterica serovar Typhimurium. However, a causative genotype could not be identified to explain this observed phenotype. This study provides insights into the S. Panama isolates circulating in Australia over two-decades, finding that 78% were linked to international travel suggesting importation in Australia. It shows MDR was common in this iNTS serovar, and colistin resistance reported for the first time. It provides the first data on the host-pathogen interactions of S. Panama in Australia, which will aid our collective understanding of the pathobiology of S. Panama and iNTS serovars more broadly.